Soil solution compositions and mineralogy of some active acid sulfate soils in Malaysia as affected by laboratory incubation with lime - Shamshuddin, J.; Auxtero, E.A. (Ovid Technologies (Wolters Kluwer Health), 1991)
Acid sulfate soils in Malaysia are developed when pyrite bearing deposits in the coastal plains are drained for agricultural production. The soils are characterized by low pH and the presence of yellowish jarosite mottles. The mechanism of the formation of this jarosite is studied. Acid sulfate soils from Pulau Lumut, Selangor, Malaysia were used to assess chemical and mineralogical transformations in the soils as affected by drainage and liming. Soil solutions at field capacity were extracted and characterized, and soil minerals were studied by X-ray diffraction analysis, transmission electron microscopy, and scanning electron microscopy. It was observed that jarosite crystal size was about 1 μm. This jarosite is believed to form via chemical precipitation in the solution containing sufficient activities of Al3+, K+, Fe3+, and SO42−. Drainage also resulted in the formation of other hydroxy-sulfate minerals. Lime application changed the activities of metals and ligands in the soil solution, affecting the formation of the hydroxy-sulfates.